Meta-Analysis: Shouldn’t Prophylactic Corticosteroids be Administered During Cardiac Surgery with Cardiopulmonary Bypass? - Chai, Tianci; Zhuang, Xinghui; Tian, Mengyue; Yang, Xiaojie; Qiu, Zhihuang; Xu, Shurong; Cai, Meiling; Lin, Yanjuan; Chen, Liangwan (Frontiers in Surgery, 2022)
Background: Corticosteroids can effectively inhibit systemic inflammation induced by cardiopulmonary bypass. Recently clinical trials and meta-analyses and current guidelines for cardiac surgery do not support corticosteroids prophylaxis during cardiac surgery because of an increase in myocardial infarction and no benefit for patients. The aim of this study is to determine whether specific corticosteroids dose ranges might provide clinical benefits without increasing myocardial infarction. Methods: The PubMed, Web of Science, Embase, Clinical Trials, and Cochrane databases were searched for randomized controlled trials (RCTs) published before August 1, 2021. Results: 88 RCTs with 18,416 patients (17,067 adults and 1,349 children) were identified. Relative to placebo and high-dose corticosteroids, low-dose corticosteroids (≤20 mg/kg hydrocortisone) during adult cardiac surgery did not increase the risks of myocardial infarction (odds ratio [OR]: 0.96, 95% confidence interval [CI]: 0.43–2.17; p=0.93). However, low-dose corticosteroids were associated with lower risks of atrial fibrillation (OR: 0.58, 95% CI: 0.44–0.76; p<0.0001) and kidney injury (OR: 0.29, 95% CI: 0.09–0.96; p=0.04). Furthermore, low-dose corticosteroids significantly shortened the mechanical ventilation times (mean difference [MD]: –2.74 h, 95% CI: –4.14, –1.33; p=0.0001), intensive care unit (ICU) stay (MD: –1.48 days, 95% CI: –2.73, –0.22; p=0.02), and hospital stay (MD: –2.29 days, 95% CI: –4.51, –0.07; p=0.04). Conclusion: Low-dose corticosteroids prophylaxis during cardiac surgery provided significant benefits for adult patients, without increasing the risks of myocardial infarction and other complications.